Catalytic Asymmetric Synthesis of Phosphoryl‐1, 4‐dihydropyridazines via an Enantioselective Allylic Alkylation/1, 3‐Dipolar Cycloaddition/Rearrangement Reaction Sequence. Issue 14 (8th July 2016) - Du, Fei; Yin, Liyang; Ning, Yanqiang; Peng, Yungui
Abstract: A novel methodology has been developed for the synthesis of chiral phosphoryl‐1, 4‐dihydropyridazine derivatives based on an asymmetric allylic alkylation/intramolecular 1, 3‐dipolar cycloaddition/rearrangement reaction sequence, various chiral 3‐phosphoryl‐4‐aryl‐1, 4‐dihydropyridazine‐5‐carboxylates were achieved in high yields with high enantioselectivities. Moreover, chiral 4, 5‐dihydropyridazinone derivatives were also facilely furnished by the reduction of the allylic alkylation products of Morita–Baylis–Hillman carbonates and α‐diazophosphonates. Abstract :